STRATEGI PENGEMBANGAN USAHA BUDIDAYA TAMBAK YANG BERKELANJUTAN DI DESA LAWALLU KABUPATEN BARRU - Nurtjahyan Husain; Rustam Rustam; Abdul Rauf (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2020)
This study aims to determine the level of socioeconomic feasibility of the pond cultivation business and formulate a sustainable development policy strategy for the pond cultivation business in the Lawallu village of Barru Regency. who works as a shrimp farmer in Lawallu Village. Analysis of the data used consists of business feasibility analysis (profit analysis, NPV, IRR, Net B / C, BEP), analysis of community social conditions and SWOT analysis.The results showed that the profit analysis was able to produce a large enough value based on the results of that the average net income or the benefits that could be generated from this aquaculture business could reach IDR. 21,165,179 per cycle and IDR. 84,660,714 per year. From the acquisition of each investment analysis shows the analysis of investment criteria obtained NPV values> 0, net B / C> 1 and IRR> of the applicable interest rate (11%), so it can be concluded from the pond cultivation business in Lawallu Village Barru Regency has high feasibility to be developed. From the results of the analysis and discussion of the prospects for developing a pond aquaculture business in Lawallu Village by using a SWOT matrix based on internal and external factors that exist in a traditional pond business there are 9 strategies to be developed.